2019
DOI: 10.1002/ejp.1365
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal neuropathic pain development and maintenance in rats are suppressed by a positive modulator of α6 GABAA receptors

Abstract: γ‐Aminobutyric acid type A (GABAA) receptors containing the α6 subunit are located in trigeminal ganglia, and their reduction by small interfering RNA increases inflammatory temporomandibular and myofascial pain in rats. We thus hypothesized that enhancing their activity may help in neuropathic syndromes originating from the trigeminal system. Here, we performed a detailed electrophysiological and pharmacokinetic analysis of two recently developed deuterated structurally similar pyrazoloquinolinone compounds. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…α6-containing GABAA receptors have been reported to contribute to the alleviation of sensorimotor gating deficits (Chiou et al, 2018 ) and orofacial pain and migraine (Fan et al, 2018 ) in animal and cell models. Moreover, models of essential tremor and trigeminal neuropathic pain also have been demonstrated to benefit from drugs that act on α6-containing GABAA receptors (Handforth et al, 2018 ; Vasović et al, 2019 ). α6βγ2-containing receptors can be discriminated from α1βγ2, α2βγ2, α3βγ2, and α5βγ2 since they are not sensitive to diazepam.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…α6-containing GABAA receptors have been reported to contribute to the alleviation of sensorimotor gating deficits (Chiou et al, 2018 ) and orofacial pain and migraine (Fan et al, 2018 ) in animal and cell models. Moreover, models of essential tremor and trigeminal neuropathic pain also have been demonstrated to benefit from drugs that act on α6-containing GABAA receptors (Handforth et al, 2018 ; Vasović et al, 2019 ). α6βγ2-containing receptors can be discriminated from α1βγ2, α2βγ2, α3βγ2, and α5βγ2 since they are not sensitive to diazepam.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that α6 subunits are recruited for the strengthening of synapses and added to α1 subunit containing postsynaptic densities (Accardi et al, 2015 ). Recent research has identified a number of putative pathophysiological roles which involve α6-containing receptors, and targeting these is considered an interesting strategy for disorders with sensorimotor gating deficits (Chiou et al, 2018 ), essential tremor (Handforth et al, 2018 ), and by way of receptors thought to be localized in the trigeminal ganglia, trigeminal neuropathic pain states (Puri et al, 2012 ; Vasović et al, 2019 ) and migraine (Fan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both host and bacteria can convert glutamate to GABA [ 71 ]. Some previous studies reported that agents promote the release of GABA by activating GABA receptors, thus effectively relieving trigeminal and diabetic-related NP [ 72 , 73 ]. Braz et al demonstrated that GABAergic precursor cell transplantation can reverse allodynia in a mouse NP model and propose transplantation as a therapeutic option in various NP-related models [ 74 , 75 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the paper [93], the α6 subunit of the GABAARs located in trigeminal ganglia was tested as a possible target for management of trigeminal neuropathic pain. The effect of two pyrazoloquinolinone compounds, DK-I-56-1 and DK-I-87-1 was studied, and one of them, DK-I-56-1, was shown to have a therapeutic potential.…”
Section: Targets Of Analgesic and Antipruritic Therapymentioning
confidence: 99%